2006 1st International Conference on Communication Systems Software &Amp; Middleware
DOI: 10.1109/comswa.2006.1665217
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lexical Analysis Tools for Buffer Overflow Detection in Network Software

Abstract: Abstract-Many of the bugs in distributed software modules are security vulnerabilities, the most common and also the most exploited of which are buffer overflows and they typically arise in programs written in the C language. This paper, focusing on static analysis tools for detecting buffer overflows in C programs, presents a methodology for experimentally evaluating and comparing the main objective features of such tools. The proposed method is based on testing all the tools on a common set of publicly avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Take most common tools with high efficiency (Its4, Rats, Flawfinder) for example, David Pozza's research indicated [6] that, when being tested with the same software package, Flawfinder found the most vulnerabilities, but did not totally cover those found by Rats and Its4; numbers of vulnerabilities found by Rats and Its4 are close, but many of them are not the same. Thus if each static analysis tool's advantages can be made full use of, and output data of these tools' analysis results can be fused in a proper way, to let the vulnerabilities sets verify and complement each other, and surely a better result comes out.…”
Section: The Reason For This Methodsmentioning
confidence: 99%
“…Take most common tools with high efficiency (Its4, Rats, Flawfinder) for example, David Pozza's research indicated [6] that, when being tested with the same software package, Flawfinder found the most vulnerabilities, but did not totally cover those found by Rats and Its4; numbers of vulnerabilities found by Rats and Its4 are close, but many of them are not the same. Thus if each static analysis tool's advantages can be made full use of, and output data of these tools' analysis results can be fused in a proper way, to let the vulnerabilities sets verify and complement each other, and surely a better result comes out.…”
Section: The Reason For This Methodsmentioning
confidence: 99%
“…According to the literatures, it is pointed that flaw finder finds most of vulnerabilities, but not completely includes vulnerabilities found by RATS and ITS4 aimed to the same software package. The quantity of vulnerabilities found by RATS and ITS4 have a smaller difference, but with many disjoint sets [8]. Splint is adopted to detect modular for the C language [9].…”
Section: A the Main Ideamentioning
confidence: 99%
“…Moreover, programming languages, which are likely to make the programming task easier, are still frequent to error prawn. This is because of either the new languages' features do not exclude all the causes of errors or C, C++, etc like some old languages are in use [4,7,9].…”
Section: Optimization Issuesmentioning
confidence: 99%
“…For grammatically incorrect input string, the parser declares the detection of syntax error. No parse tree [7] in this case is generated. As an alternative to parsing, based on the repetitive application of regular expressions using a shortest-match strategy, we may apply an iterative lexical technique.…”
Section: Parser Generatormentioning
confidence: 99%